PENYULUHAN TENTANG KESADARAN TERHADAP PENTINGNYA AKTIVITAS FISIK PADA PENURUNAN CIDERA ANKLE DI PHYSIOMOVECARE RS EFARINA BERASTAGI - I Ngurah Gede Verar Fujastawan; Isa Harpika Br. Ginting; Ilham Irwansyah (Yayasan Nusantara Hasana Berdikari, 2024)
This community service report aims to enhance public awareness—especially among prospective athletes, college students, and the general community—of the importance of physical activity as a preventive measure against ankle injuries. In the context of the high prevalence of ankle injuries, one of the most common musculoskeletal injuries across various segments of the population , this outreach activity was conducted at Physiomovecare RS Efarina Berastagi. The program involved delivering theoretical presentations on ankle injuries, the significance of regular physical activity, and practical demonstrations of strengthening exercises designed to reduce injury risks. The outcomes of the outreach indicate an increase in participants’ knowledge as well as improved attitudes towards maintaining physical fitness and regular physical activity. This report is structured following the standard guidelines for community service reports, covering introduction, literature review, methodology, results, and conclusion